Social entrepreneurship in Asia: a literature review - Savita Shankar (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
This paper reviews the literature in peer-reviewed journals on social enterprises in South, East and Southeast Asia. The country studies indicate that evolution of social enterprises in a country seems to be closely related to historical events that create favorable conditions. Typologies of social enterprises that develop in a country appear to be a result of its socio-economic circumstances, cultural factors and regulatory environment. The literature on social enterprises in the Asian context is largely limited to some studies on development of social enterprise in specific countries and conceptual papers in which the Grameen Bank case features as an example. This limited nature of the literature is a surprising finding if one were to consider the current level of social enterprise activity in Asia. The short history of social entrepreneurship research, the difficulties in developing a working definition of a social enterprise and the dominance of Western debates in the social entrepreneurship literature have all contributed to the lack of adequate literature based on empirical studies in Asia. The deeply embedded nature of social enterprises and the development potential they hold are important reasons for addressing this research gap.